A novel cyanobiphenyl benzothiazole-based fluorescent probe for detection of biothiols with a large Stokes shift and its application in cell imaging. Issue 5 (2nd February 2017) - Chen, Song; Li, Hongmei; Hou, Peng
Abstract: An ESIPT-based fluorescent probe (Probe1 ) with a large Stokes shift (202 nm) for the sensing of biothiols has been developed based on cyanobiphenyl benzothiazole derivative exhibiting larger Stokes shift than 2-(benzothiazol-2-yl)phenol. This probe with 2, 4-dinitrobenzenesulfonate (DNBS) as a highly thiol-selective group was constructed based on the combination of excited state intramolecular proton transfer (ESIPT) and photoinduced electron transfer (PET) mechanisms. Upon the treatment with biothiols, this probe produced a remarkable fluorescence enhancement at 482 nm. The detect limits for Cys, GSH and Hcy was calculated to be as low as 2.0 × 10 −8  M, 1.7 × 10 −7  M and 1.2 × 10 −7  M, respectively (based on S/N = 3). Importantly, application of this probe was successfully demonstrated by imaging thiols in living NCI-H226 cells. Graphical abstract: An ESIPT-based fluorescent probe with a large Stokes shift (202 nm) for the sensing of biothiols has been developed based on cyanobiphenyl benzothiazole derivative exhibiting larger Stokes shift than 2-(benzothiazol-2-yl)phenol.